In Vitro Anatomical Models for Nasal Drug Delivery - Gerallt Williams; Julie D. Suman (MDPI AG, 2022)
Nasal drug delivery has been utilized for locally acting diseases for decades. The nose is also a portal to the systemic circulation and central nervous system (CNS). In the age of SARS-CoV2, the development of nasal sprays for vaccination and prophylaxis of respiratory diseases is increasing. As the number of nasal drug delivery applications continue to grow, the role of targeted regional deposition in the nose has become a factor is nasal drug development. In vitro tools such as nasal casts help facilitate formulation and product development. Nasal deposition has been shown to be linked to pharmacokinetic outcomes. Developing an understanding of the complex nasal anatomy and intersubject variability can lead to a better understanding of where the drug will deposit. Nasal casts, which are replicas of the human nasal cavity, have evolved from models made from cadavers to complex 3D printed replicas. They can be segmented into regions of interest for quantification of deposition and different techniques have been utilized to quantify deposition. Incorporating a nasal cast program into development can help differentiate formulations or physical forms such as nasal powder versus a liquid. Nasal casts can also help develop instructions for patient use to ensure deposition in the target deposition site. However, regardless of the technique used, this in vitro tool should be validated to ensure the results reflect the in vivo situation. In silico, CFD simulation or other new developments may in future, with suitable validation, present additional approaches to current modelling, although the complexity and wide degree of variability in nasal anatomy will remain a challenge. Nonetheless, nasal anatomical models will serve as effective tools for improving the understanding of nasal drug delivery.